Proceso de atención de enfermería en gestante de 34.4 semanas de 31 años, con preeclampsia leve. - Franco Salvatierra, Ruth Tavita (2020)
The clinical case presented below is intended to make you aware of the importance of detecting and appropriately treating preeclampsia before the onset of seizures (eclampsia) or other life-threatening complications. For this reason, this case study is carried out, in a 31-year-old pregnant patient, with 34.4 weeks of gestation hospitalized in the delivery room of the Hospital Sagrado Corazón De Jesús with a diagnosis of mild pre-eclampsia who collaborated with the necessary information to perform the interventions precise, the same q has been very useful to carry out this work. Through the analysis, the patient's health problem was identified in order to improve medical and nursing management, which must be timely, based on a comprehensive assessment that ensures maternal-fetal well-being, in such a way that they know the risk factors that can give rise to this pathology, and its possible complications.